2006
DOI: 10.1159/000096386
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders in Single and Multiple Sexual Murderers

Abstract: Background: Sexual homicides – and particularly offenders with multiple victims – receive much attention in the general public as well as among forensic experts. The aim of this study was to assess psychiatric disorders in a large sample of sexual murderers and to identify disorders related to multiple sexual homicides. Sampling and Methods: Psychiatric court reports from 20 German forensic psychiatrists on 166 men who had committed a sexual homicide were evaluated for psychiatric disorders according to DSM-IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 53 publications
(59 reference statements)
6
53
0
9
Order By: Relevance
“…Research has shown that mentally ill individuals are at a higher risk of violence, including homicide (Schanda et al, 2004). Furthermore, numerous disorders have been found in samples of sexual homicide offenders (Hill, Habermann, Berner, & Briken, 2007). This research is one of the very few (see also Beasley, 2004) that gather psychological measure data from the actual killer to better understand the underlying persona of one particular inmate.…”
Section: Why Is This Research Important?mentioning
confidence: 99%
“…Research has shown that mentally ill individuals are at a higher risk of violence, including homicide (Schanda et al, 2004). Furthermore, numerous disorders have been found in samples of sexual homicide offenders (Hill, Habermann, Berner, & Briken, 2007). This research is one of the very few (see also Beasley, 2004) that gather psychological measure data from the actual killer to better understand the underlying persona of one particular inmate.…”
Section: Why Is This Research Important?mentioning
confidence: 99%
“…As our cases, victims are usually females [9,13], but sex related homicides can involve, as well as, heterosexual and homosexual relationships [8,32]. Generally, most of the victims (65-90%) are strangers or casual acquaintances, rather than a consensual sexual partner of the offenders [8].…”
Section: Discussionmentioning
confidence: 93%
“…Compared to non-sexual homicide offenders, psychopaths are significantly more likely to commit sexual homicide [8]. Indeed, personality disorder, psychopathy, paraphilia, paraphiliarelated disorders and sadistic sexual fantasy may, usually, explain this terrible form of violence [9].…”
Section: Introductionmentioning
confidence: 99%
“…Most rapists do not have paraphilias and very few are sexually sadistic. However, up to 80% of sexual murderers have paraphilias (Hill 2007;Proulx 2007).…”
Section: Sexual Disordersmentioning
confidence: 99%